Allopurinol hepatotoxicity is associated with human leukocyte antigen Class I alleles. (7th May 2021) - Fontana, Robert J.; Li, Yi‐Ju; Phillips, Elizabeth; Saeed, Naba; Barnhart, Huiman; Kleiner, David; Hoofnagle, Jay
Abstract: Background/Aims: Allopurinol can cause HLA class I‐associated life‐threatening severe skin reactions. However, HLA risk and association with clinical features in allopurinol hepatotoxicity are unknown. Methods: Eleven of 17 patients with suspected allopurinol hepatotoxicity enrolled into the Drug‐Induced Liver Injury Network were adjudicated as definite, highly likely, or probable. High‐resolution HLA sequencing was undertaken in cases and compared with population and other DILI controls. Result: Median age was 60 years, 54% were male, and 63% African‐ American, 27% Caucasian, and 9% Hispanic. Patients presented at a median of 52 days after starting allopurinol, all were hospitalized and six were jaundiced. The median peak ALT, alkaline phosphatase, and total bilirubin were 525 U/L, 521 U/L, and 7.8 mg/dl, respectively, with a median R ratio of 2.7 at onset. During follow‐up, nine patients were treated with corticosteroids including five of the six with suspected DRESS. Three patients died including two from liver failure at 38 and 45 days after onset, and the remaining eight recovered. Three HLA alleles were found to be overrepresented in allopurinol cases, particularly in African Americans: HLA‐B*58:01, which has been previously linked to severe skin reactions, and HLA‐B*53:01 and HLA‐A*34:02, all of which are more frequently found in African Americans than European Americans or Latinos. Conclusions: Allopurinol hepatotoxicity is associated with systemic hypersensitivity, a short latency to onset, African‐American race and three HLA risk alleles, HLA‐B*58:01, HLA‐B*53:01, and HLA‐A*34:02‐58:01 testing may help confirm a diagnosis of hepatotoxicity in allopurinol‐treated patients.